(untitled) (Konturen, 2026)
This article examines the elusive status of the child in Franz Kafka’s work as a way of looking back at the future. Unlike Kafka’s bachelorhood, his childlessness has received less critical attention. In Kafka’s oeuvre, the closest we get to paternity is the mysterious, childlike specters that haunt the apartments of lonely bachelors, staging not only the problem of what Lee Edelman terms “reproductive futurism” but also the collision between literary modernism and realism. Yet, Kafka’s unfinished novel Amerika: The Missing Person [Der Verschollene] introduces a counterweight to the proliferation of childless bachelors: the juvenile but absent father. Kafka’s America represents a prelapsarian state both by allowing Karl to escape his primordial sin—a child born out of wedlock—and by indefinitely extending his youth, thus transforming the precocious father into a perpetual child. Like Kafka’s bachelor stories, The Missing Person is pervaded by strange bodily gestures that highlight the fantastical contortions of Kafka’s narrative world and his departure from the conventions of literary realism. These gestures are Kafka’s way of contemplating another possible world—or future—not bound by the quotidian, heteronormative teleology of family life.